Effect of feedings with different protein levels and dietary supplemental rElGH on culture performances of sex reversed Oreochromis niloticus (Linnaeus, 1758) - Muhammad Safir; alimuddin alimuddin; Mia Setiawati; muhammad Agus Suprayudi; Muhammad Zairin Junior (Depik, 2022)
This study aims to evaluate the culture performance of tilapia (Oreochromis niloticus) that have been treated with 17α-methyltestosterone (MT) and without MT (w-MT), feed with different protein levels (20, 24, and 28%) and recombinant Epinephelus lanceolatus growth hormone (rElGH)-diet. The research was conducted in 9 treatments and triplicate. Tilapia larvae were soaked twice, totaling 500 larvae, at the age of 10 days after hatching (DAH) and the age of 14 DAH was soaked for 4 hours using 1/l MT 2 mg/l solution. Fish maintenance was conducted in an aquarium of 1.0x0.5x0.5 m3 in the first month, and three months later in net cages (2.0x2.0x1.5 m3). Daily growth rate (DGR) and biomass gain (BG) were increased in line with increasing feed protein content and rElGH supplementation. The highest DGR and BG values were MT+28+rElGH (P 0.05) treatment. The highest feed consumption and the lowest feed conversion ratio were also obtained in the MT+28+rElGH treatment (P 0.05). Fish survival was ranged from 79.89 to 90.28% (P 0.05). The highest profit potential was found in the MT+28+rElGH treatment. The efficient aquaculture can be obtained by feeding sex-reversed tilapia at a protein level of 28% and a diet supplemented with rElGH.Keywords:Feed conversion ratioGrowth hormoneProtein retention17α-methyltestosterone